Identification and characterization of a new sulfoacetaldehyde reductase from the human gut bacterium Bifidobacterium kashiwanohense. Issue 6 (20th June 2019) - Zhou, Yan; Wei, Yifeng; Nanjaraj Urs, Ankanahalli N.; Lin, Lianyun; Xu, Tong; Hu, Yiling; Ang, Ee Lui; Zhao, Huimin; Yuchi, Zhiguang; Zhang, Yan
Abstract : Hydroxyethylsulfonate (isethionate (Ise)) present in mammalian tissues is thought to be derived from aminoethylsulfonate (taurine), as a byproduct of taurine nitrogen assimilation by certain anaerobic bacteria inhabiting the taurine-rich mammalian gut. In previously studied pathways occurring in environmental bacteria, isethionate is generated by the enzyme sulfoacetaldehyde reductase IsfD, belonging to the short-chain dehydrogenase/reductase (SDR) family. An unrelated sulfoacetaldehyde reductase SarD, belonging to the metal-dependent alcohol dehydrogenase superfamily (M-ADH), was recently discovered in the human gut sulfite-reducing bacterium Bilophila wadsworthia ( Bw SarD). Here we report the structural and biochemical characterization of a sulfoacetaldehyde reductase from the human gut fermenting bacterium Bifidobacterium kashiwanohense ( Bk TauF). Bk TauF belongs to the M-ADH family, but is distantly related to Bw SarD (28% sequence identity). The crystal structures of Bk TauF in the apo form and in a binary complex with NAD + were determined at 1.9 and 3.0 Å resolution, respectively. Mutagenesis studies were carried out to investigate the involvement of active site residues in binding the sulfonate substrate. Our studies demonstrate the presence of sulfoacetaldehyde reductase in Bifidobacteria, with a possible role in isethionate production as a byproduct of taurine nitrogen assimilation.